2011
DOI: 10.1210/jc.2010-0130
|View full text |Cite
|
Sign up to set email alerts
|

Hyperandrogenism in Women with Polycystic Ovary Syndrome Persists after Menopause

Abstract: In postmenopausal PCOS women, ACTH and cortisol responses to CRH are normal. Androgen levels at baseline are higher in PCOS than control women and remain increased after ACTH stimulation. The dexamethasone suppression results in postmenopausal PCOS women suggest that DHEAS and total T are partially of adrenal origin. Although the ovarian contribution was not fully assessed, increased Δ(4)A production suggests that the ovary also contributes to hyperandrogenism in postmenopausal PCOS women. In conclusion, postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 32 publications
3
43
0
2
Order By: Relevance
“…Although normal androgen cut-off levels have not been precisely established for menopause, it is generally accepted that they do not exceed those of premenopausal women (6,13). However, androgen levels are consistently higher in patients with nontumorous hyperandrogenism compared with nonhyperandrogenic postmenopausal women (14,15). Relative and occasionally absolute hyperandrogenism in postmenopause, defined as testosterone levels only modestly O40 ng/dl, is most commonly the result of nontumorous causes which usually pre-exist and may be aggravated by the physiological changes occurring in menopause (7).…”
Section: Causes Of Hyperandrogenism After Menopausementioning
confidence: 99%
See 2 more Smart Citations
“…Although normal androgen cut-off levels have not been precisely established for menopause, it is generally accepted that they do not exceed those of premenopausal women (6,13). However, androgen levels are consistently higher in patients with nontumorous hyperandrogenism compared with nonhyperandrogenic postmenopausal women (14,15). Relative and occasionally absolute hyperandrogenism in postmenopause, defined as testosterone levels only modestly O40 ng/dl, is most commonly the result of nontumorous causes which usually pre-exist and may be aggravated by the physiological changes occurring in menopause (7).…”
Section: Causes Of Hyperandrogenism After Menopausementioning
confidence: 99%
“…In women with PCOS, symptoms usually start in adolescence and gradually progress during reproductive years (24), with their severity depending on the presence of IR and obesity that is also associated with an increased risk for metabolic abnormalities (25). Although in perimenopause there is an amelioration of the clinical and laboratory features of PCOS (26,27), elevated androgen levels of both ovarian and adrenal origin continue to persist during early postmenopause (14) and remain elevated up to late menopause without exceeding premenopausal levels (28). Although other androgens such as androstanediol glucuronide may also be implicated particularly in the development of hirsutism, there is no data on their potential effect in postmenopausal women with PCOS (29).…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have found low levels of SHBG and high androgenicity to be associated with dyslipidemia and increased carotid artery intima-media thickness, which in turn is associated with an adverse CVD risk factor profile in postmenopausal women (88)(89)(90), evidence for an association with hard cardiovascular endpoints especially among diabetic women in longitudinal studies is lacking. While the source of the excess androgens in diabetic women has not been studied in detail, results in women with polycystic ovary syndrome (PCOS), who are also more likely to be obese and insulin resistant (91,92), suggest an ovarian source of androgens in diabetics, although increased adrenal steroid production might also contribute in part to the higher androgen levels reported in diabetic women (93). Moreover, the ovaries in diabetics may have a reduced ability to convert androgens to estrogens due to a reduction in ovarian aromatase activity (94).…”
Section: Rationale and Significance Of The Studymentioning
confidence: 99%
“…Additionally, the ovaries in diabetic women may have reduced ability to convert androgen to estrogen due to reduction of ovarian aromatase activity (94). Evidence obtained from women with polycystic ovary syndrome (PCOS), who are usually insulin resistant and at high risk for glucose intolerance, further suggests an ovarian source of hyperandrogenemia in diabetic women (93). Even when adrenal androgen secretion is suppressed by dexamethasone administration, women with PCOS still exhibit higher androgen levels than normal healthy women, suggestive of an ovarian origin of androgen excess (299,300).…”
Section: Hypothesis Onementioning
confidence: 99%